Importance of scientific initiation and extension projects for undergraduate nursing (Research, Society and Development, 2022)
Objective: To present the importance of research in the academic life of students in the undergraduate nursing course at a public university in the interior of Amazonas. Methodology: This is an experience report, resulting from the experiences of students of the Undergraduate Nursing Course (CGE) of the Institute of Health and Biotechnology (ISB) of the Federal University of Amazonas (UFAM). This report describes an experience about the participation of students in the institutional program of scholarships for scientific initiation - PIBIC. In addition, research was developed in the modality Institutional Program of Scholarships for Extension (PIBEX) and Program Curricular Activity of Extension (PACE). The research and activities were developed during the bachelor's degree course in nursing at the ISB/UFAM Campus in the municipality of Coari in the interior of Amazonas. Results: The scientific initiation and university extension were fundamental in the development of students in academic production, adding new knowledge and improving their skills with research. In addition, they produced important contributions to science and showed the great potential of developing investigations as undergraduates. Final Considerations: In view of this, it is important to emphasize how fundamental research is in the academic environment with undergraduates; the university is not merely an institution of higher education courses, but also of promoting and encouraging the development of research and extension through existing programs. Thus, allowing the advancement of science through new research being developed by academics.